Estrogenic Effects of Kebar Grass (Biopyhtum Petersianum) in 96% Ethanol Extract and Various Solvent Fractions - Mulyati Effendi; Yulianita; Herlina, Nina; Nurhikmah, Wilda (Jurnal Jamu Indonesia, 2022)
This study aimed to compare antioxidant, antibacterial and toxicity tests of various types of kesambi tree bark extract (Schleichera oleosa (Lour) Oken). The research stages included extraction of kesambi stem skin from Mancak Serang sub-district with multilevel maceration techniques using 3 solvents: Methanol, n-hexane, and ethyl acetate. The extract was then tested for antioxidant activity, antibacterial, and toxicity. The results of antioxidant testing using the DPPH method, antibacterial with agar diffusion method, and toxicity test with BSLT method, the results showed that ethyl acetate extract had better antioxidant activity (IC50 7,723 ppm.) compared to extract of methanol (IC50 7,801 ppm), and n-hexane extract (IC50 8,568 ppm). Antibacterial activity showed the ability to inhibit the growth of Streptococcus aureus compared to Escherichia coli at a concentration of 10000 ppm, and the results of the toxicity test showed that ethyl acetate extract had better activity (LC50 305,17 ppm) than n-hexane extract (LC50 374, 96 ppm) and methanol extract (LC50 431,26 ppm).